The Qualified Islamic Religious Education Teachers as a Foundation in Learning at MI - Muhammad Nurul Arifin; Muhammad Wahzudi (eL Bidayah: Journal of Islamic Elementary Education, 2020)
MI teachers especially those who teach Islamic Religious Education will have to do with the morals of students, where the benchmark of the final results of PAI education is the application of PAI in the daily lives of students, the success or failure of students in PAI learning can be seen from the attitudes of students, research using the research method of literature by using content analysis techniques from the literature. PAI teacher must know the characteristics of MI students, know the change in behavior from learning outcomes, learning achievement, teacher competence, and also must be able to understand and learn about how a good PAI teacher, so that when the PAI teacher already knows and even masters it, the PAI teacher can improve its quality, so that it can be used as a foundation to sustain the change in attitude of students in primary schools especially the scope of Madrasah Ibtidaiyah. [Guru MI khususnya yang mengajar Pendidikan Agama Islam akan ada kaitannya dengan akhlak peserta didik, dimana patokan dari hasil akhir pendidikan PAI adalah penerapan PAI di keseharian peserta didik, berhasil tidaknya peserta didik dalam pembelajaran PAI dapat dilihat dari sikap peserta didik, penelitian menggunakan metode penelitiaan keputakaan dengan menggunakan teknik Analisis isi dari kepustakaan tersebut. guru PAI harus mengetahui karakteristik siswa MI, mengetahui perubahan perilaku dari hasil belajar, maniestasi belajar, kompetensi guru, dan juga harus bisa mengerti dan mempelajari tentang bagaimana guru PAI yang baik, sehingga ketika guru PAI tersebut sudah mengetahui bahkan menguasai hal tersebut maka guru PAI dapat meningkatkan kualitasnya, sehingga mampu dijadikan pondasi untuk menopang perubahan sikap peserta didik di sekolah dasar khusunya lingkup Madrasah Ibtidaiyah]